Effect of Optaflexx and days on feed on feedlot performance, carcass characteristics, and skeletal muscle gene expression in yearling steers - Winterholler, S.J.; Parsons, G.L.; Sissom, E.K.; Hutcheson, J.P.; Swingle, R.S.; Johnson, B.J. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Two-thousand two-hundred fifty-two yearling steers (690 lb) were used to evaluate the effects of Optaflexx and days on feed on finishing steer performance and carcass characteristics. Treatment groups included serial harvest dates of 150, 171, or 192 days. Within each harvest date, steers either received Optaflexx (200 mg/steer daily of ractopamine-HCl) for the final 28 days, or did not receive Optaflexx. All steers were initially implanted with Revalor-IS and were re-implanted with Revalor-S after 75 days on feed. At harvest, muscle samples from the inside round were obtained for mRNA analysis of the β- adrenergic receptors (AR). Optaflexx increased daily gains, hot carcass weight, and ribeye area, and improved feed efficiency. Optaflexx did not affect dressing percentage, USDA yield grade, or quality grade. Optaflexx did not change overall feed intake across the entire feeding period, but feed intake was increased during the 28-day period that steers received Optaflexx. As expected, greater days on feed decreased daily gains, overall feed intake, and the number of yield grade 1 and 2 carcasses, and worsened feed efficiency. Also, greater days on feed increased hot carcass weight, dressing percentage, and the number of prime and choice carcasses, as well as the number of yield grade 4 and 5 carcasses. Increasing days on feed decreased the abundance of mRNA for β1-AR and β3-AR, and increased the abundance of β2-AR mRNA. Optaflexx had no effect on abundance of mRNA for β1-AR or β3-AR, but it increased the abundance of mRNA for β2-AR. Optaflexx may affect expression of the β2-AR gene in skeletal muscle, which could impact the performance responses to Optaflexx feeding in steers.
Keywords: Beef; Optaflexx; Carcass characteristics; Skeletal muscle gene expression; Yearling steers